Rasayana Therapy –Tool For Healthy Ageing - Jain, Trupti (International Research Journal of Ayurveda & Yoga, 2021)
In recent years, due to advanced healthcare facilities Life Expectancy around the world has been increasing steadily, but this achievement has been possible only in terms of chronological ageing. The increase expectancy of life is now associated with several health problems which definitely affects persons quality of life. We all know that ageing is an inevitable phenomenon, so people are searching strategies for healthy ageing. Ayurveda is the only science which described a branch devoted to study of ageing & its prevention under the heading of “ Rasayana Tantra”. Rasayana therapy (Rejuvenation)is mainly a science of nutrition which improves immunity of body against diseases. On the basis of current level of understanding Rasayana (Rejuvenation) has adaptogenic property, anabolic activity, immunomodulatory effects and antioxidant effect. So, if it should be adopted in systematic manner from early onset of life, it delays ageing process and causes healthy ageing.